Structural optimization of pit bionic drip irrigation emitter to improve hydraulic performance and anti-clogging performance - Zhen Zhao; Tianyu Xu; Yanru Su; Sanlin Bao; Qiuyue Yu (PLoS ONE, 2025)
The blockage inside the flow channel of drip irrigation emitters is a key issue that restricts their usability. The low-speed vortex zone that exists in traditional channel design is the core reason. This study designed four different structures of pit bionic drip irrigation emitters based on the principles of plant bionics. The computational fluid dynamics (CFD) numerical simulation method was adopted and the flow velocity and turbulence energy of four structures were analyzed. The discrete element method (DEM) was combined to study the motion trajectory of 0.1 mm sand particles. The results indicate that schemes 1, 2, and 4 all have significant low-speed vortices in the return water zone (D zone). The situation in scheme 3 is relatively mild and the probability of sand particles depositing in the channel decreases. The flow channel structure was further optimized based on the original foundation and eight types of sand particles with different sizes were selected for anti clogging experiments. The relative traffic of the optimized model in the third and fourth stages was 13.34% and 14.51% higher. In terms of the sensitive particle size causing blockage, the maximum allowable particle size of the optimized flow channel structure was nearly twice that of scheme 3. When the particle size was 0.120, 0.165, 0.187, 0.212, and 0.245 mm, the sedimentation rate was reduced by an average of 58.02%. This study confirms that optimized drip irrigation emitters have better anti clogging performance under multiple particle size drip irrigation conditions.